2017
DOI: 10.1038/s41598-017-07885-3
|View full text |Cite
|
Sign up to set email alerts
|

The saliva microbiome profiles are minimally affected by collection method or DNA extraction protocols

Abstract: Saliva has attracted attention as a diagnostic fluid due to the association of oral microbiota with systemic diseases. However, the lack of standardised methods for saliva collection has led to the slow uptake of saliva in microbiome research. The aim of this study was to systematically evaluate the potential effects on salivary microbiome profiles using different methods of saliva collection, storage and gDNA extraction. Three types of saliva fractions were collected from healthy individuals with or without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 35 publications
7
94
0
Order By: Relevance
“…Saliva samples with long storage time and multiple freezing-thawing cycles seem unsuitable for microbiota research. DNA yield from included saliva samples was lower than described in the literature (35,36) (Fig. S1).…”
Section: Resultsmentioning
confidence: 59%
“…Saliva samples with long storage time and multiple freezing-thawing cycles seem unsuitable for microbiota research. DNA yield from included saliva samples was lower than described in the literature (35,36) (Fig. S1).…”
Section: Resultsmentioning
confidence: 59%
“…Whatever the technique being employed, it is important that researchers come to a consensus on the exact procedure for collection and sequencing to ensure reproducibility. While some of these referenced studies have shown that the microbiome profile of a sample is not heavily influenced by the collection technique [78,79], these are focused on large-scale differences. However, as sequencing technologies become more efficient and microbiome-associated databases become more complete, researchers will continue to compare samples at finer scales, so minor technical variability stemming from different techniques of swabbing collection sites or using a different solution for oral rinse collections could potentially impact results.…”
Section: Technical Approaches To Study the Oral Microbiomementioning
confidence: 99%
“…Since these niches tend to have very similar overall microbiome compositions at all but the lowest taxonomic levels, many researchers choose to treat the oral cavity as an individual habitat and analyze global compositions and processes therein [10,12,112]. A few studies have shown that this is a viable and efficient method for sample collection to investigate the oral microbiome [78,79], and standardized procedures have been proposed [113,114]. Essentially, an individual would refrain from eating, drinking, brushing, or smoking (anything that might temporarily shift the typical microbial composition) for at least 30 min prior to collection.…”
Section: The Oral Cavity and Its Microbial Nichesmentioning
confidence: 99%
“…DNA yield from saliva samples was lower as compared to literature (43, 44) (Fig S1). Only a single DNA extraction had a concentration of slightly above one ng/μl (1.18; Table S4), while all other extractions had concentrations between 0.04 and 0.68 ng/μl.…”
Section: Resultsmentioning
confidence: 56%